Giant Pilomatrical Tumor With Broad Epidermal Components: An Example of Histological Diversity and a Potential Diagnostic Pitfall of Tumors With Pilomatrical Differentiation. (February 2022) - Terada, Kazuhiro; Yamada, Yosuke; Fujimoto, Masakazu; Usui, Shunya; Kogame, Toshiaki; Kaku, Yo; Moriyoshi, Koki; Haga, Hironori
Abstract : Abstract: The diagnosis of pilomatricoma, the most common matrical tumor, is generally straightforward; however, it exhibits diverse histology associated with various morphological stages and several clinical variants, and matrical differentiation can occur in various neoplastic diseases. A 56-year-old man was admitted to our hospital to resect an 11.0-cm skin tumor on his right shoulder. Because of its large size and surface irregularities, including multiple erosions and ulcers, cutaneous malignancies were clinically suspected. Histologically, the tumor formed numerous nodules with marked matrical differentiation in the superficial to deep dermis. Although the tumor was macroscopically asymmetrical and irregular, each nodule was microscopically round-shaped and consisted of basaloid cells without marked atypia, atypical mitoses, or lymphovascular invasion. Immunohistochemically, the tumor cells were positive for beta-catenin, LEF-1, and PHLDA-1, consistent with their pilomatrical differentiation. We diagnosed the case as a giant pilomatrical tumor with uncertain malignant potential, considering its "contradictory" features, namely, the worrisome histoarchitecture, such as the asymmetrical silhouette, but bland-looking cytological appearance. Unlike typical pilomatrical tumors, this tumor contained numerous epidermal components with features similar to those of the dermal components, resulting in a unique macroscopic and histological appearance. Our case broadens the known histological diversity of pilomatrical tumors.